2017
DOI: 10.1027/1864-9335/a000314
|View full text |Cite
|
Sign up to set email alerts
|

Racial Prejudice Predicts Less Desire to Learn About White Privilege

Abstract: Abstract. White people often experience unpleasant emotions in response to learning about White privilege ( Phillips & Lowery, 2015 ; Pinterits, Poteat, & Spanierman, 2009 ). Two studies (total N = 1,310) examined how race attitudes relate to White people’s desires to avoid or learn information about White privilege. White participants completed measures of their race attitudes, desire to change White privilege, and their desire to avoid learning information about White privilege. Study 1 showed that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Second, the research team examined the relevant psychological literature on Whiteness (e.g., White privilege attitudes, identity development, and costs of racism) to ascertain empirical support for these themes, modify existing themes, or identify any additional themes of White fragility. Based on this process, the research team identified and labeled six themes of White fragility: denial of privilege (Cabrera, 2014b; Knowles & Lowery, 2012; Solomona et al, 2005), avoidance (Conway et al, 2017; Phillips & Lowery, 2015), emotional reactivity (Leach et al, 2011; Utsey & Gernat, 2002), victimization (Cabrera, 2014a; Norton & Sommers, 2011), exceptionism (Chow et al, 2008; Utsey et al, 2005), and accommodation (DiAngelo & Sensoy, 2014; Lowery et al, 2007; Unzueta & Lowery, 2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the research team examined the relevant psychological literature on Whiteness (e.g., White privilege attitudes, identity development, and costs of racism) to ascertain empirical support for these themes, modify existing themes, or identify any additional themes of White fragility. Based on this process, the research team identified and labeled six themes of White fragility: denial of privilege (Cabrera, 2014b; Knowles & Lowery, 2012; Solomona et al, 2005), avoidance (Conway et al, 2017; Phillips & Lowery, 2015), emotional reactivity (Leach et al, 2011; Utsey & Gernat, 2002), victimization (Cabrera, 2014a; Norton & Sommers, 2011), exceptionism (Chow et al, 2008; Utsey et al, 2005), and accommodation (DiAngelo & Sensoy, 2014; Lowery et al, 2007; Unzueta & Lowery, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…For example, in a study on White racism with over 1,200 counselor educators, practitioners, and students, D’Andrea and Daniels (1999) found that participants deliberately refrained from engaging in anti-racist discourse to avoid emotionally heated interactions. In addition, when presented with race-centered learning opportunities, White individuals may demonstrate fragility by claiming to be sufficiently informed about issues of race and privilege (Flynn, 2015) or by rejecting information or questioning the credibility of the source (Conway et al, 2017). In particular, White individuals may present as if they “already get it” in effort to evade situations likely to stimulate discourse about racial privilege (DiAngelo, 2011).…”
Section: The Normalization Of Whitenessmentioning
confidence: 99%
“…and that racial attitudes relate to White people's desire to avoid and learn about White privilege (Conway et al, 2017). Thus, the research on racially biased reasoning has important impact on educational training and interventions aiming to increase racial awareness and decrease CBRI.…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…The desire to maintain a positive self-concept cloaks privilege and in the aggregate, practiced by many whites, creates a “herd invisibility” that protects the position of whites in the racial hierarchy (Phillips and Lowery 2018). Whites may be reluctant to acknowledge the advantages associated with whiteness (Conway et al 2017), and when confronted with the idea that they have benefited from their race, deny the existence of white privilege (Knowles et al 2014) or that it applies to them (Phillips and Lowery 2015; De Sante and Smith 2020a). In sum, white privilege denial is a subtle, but powerful, form of racial bias that maintains advantaged position of whites in the racial hierarchy and “promote[s] insensitivity and inaction with respect to racial inequality” (Knowles et al 2014).…”
Section: Racial Attitudes Old and Newmentioning
confidence: 99%